Environmental concerns and intention to practise solid waste segregation-at-source - Cheng, Kai Wah; Osman, Syuhaily; Md Jusoh, Zuroni; Lau, Nur Jasmine Leby (Malaysian Consumer and Family Economics Association, 2021)
This paper aims to analyse the egoistic concern, altruistic concern descriptively, and biospheric concern to practise solid waste segregation-at-source. A multistage sampling method was used to choose 400 respondents from the townships of Selangor’s nine districts, namely Sabak Bernam, Ulu Selangor, Kuala Selangor, Gombak, Ulu Langat, Petaling, Klang, Kuala Langat, and Sepang. A selfadministered bilingual questionnaire was used to investigate their intention to practise solid waste segregation-at-source to collect research data. The present quantitative data was then descriptively analysed using IBM SPSS Statistics 28.0. The descriptive investigation’s findings indicated that, overall, most Selangor’s households demonstrated a high level of egoistic, altruistic, and biospheric concern to practice solid waste segregation-at-source throughout the research. The current research has considerably enriched the existing scarce and limited Malaysian literature. In addition, it has significantly highlighted the better understanding of studied variables in the research area.